(untitled) (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2025)
The global transition to clean energy is accelerating demand for critical minerals – lithium, cobalt, nickel, rare earth elements – whose extraction is concentrated in high-biodiversity regions including tropical forests, alpine zones, and arid ecosystems. This creates a fundamental tension between decarbonisation imperatives and biodiversity conservation that current environmental impact assessment (EIA) frameworks are poorly equipped to resolve. This study conducted systematic biodiversity impact assessments across 84 active and proposed mining zones across 24 countries using standardised survey protocols, satellite land-cover change detection, and multi-taxon biodiversity monitoring before and up to 8 years following mining operations initiation. Mining-associated biodiversity loss within 5 km of active operations averaged -42.7% +- 8.4% for species richness and -61.4% +- 11.2% for vertebrate abundance relative to matched unimpacted reference sites. Tailings pond contamination extended aquatic biodiversity impacts up to 84.7 km downstream in river systems, substantially exceeding the 5 km buffer zones mandated by most national EIA regulations. Terrestrial connectivity disruption from haul roads and infrastructure caused significant population genetic fragmentation detectable up to 47.4 km from operations in two mammal species assessed by landscape genetics. Biodiversity offset commitments were fulfilled at only 34.7% of the 47 mines with formal offset requirements in the dataset, with unfulfilled offsets particularly concentrated in lower-income jurisdictions. Nature-inclusive mining design – including directional drilling to avoid surface disturbance in high-biodiversity areas, staged progressive rehabilitation, and catchment-level water management – reduced biodiversity impacts by 47.4% relative to conventional operations in six paired mine comparisons. These findings provide an evidence base for strengthening global mining EIA frameworks to reflect actual biodiversity impact scales and enforce offset delivery.